Multimedia package of Chinese mid autumn festival / Yeap Judy - Yeap, Judy (2001)
The Chinese mid autumn festival also called the moon festival, is not known very much outside the community. Thus,the objective of Multimedia Package Of Chinese Mid Autumn Festival is to introduce the festival more widely through a multimedia package. This package will contain the poems, songs, the food and other information of the festival. To improve the user's understanding of the after using the package, there is a quiz section to test the user. The multimedia feature combining text, graphics, video and audio together were included to increase the user's interest. A review of few existing web sites on Internet about the festival shows that all the web sites do not have multimedia feature. They are mainly text - based. After reviewing a few development tools available in the market, Macromedia Director 7.0, Macromedia Authorware 5.1 and Macromedia Flash 4.0 seem suitable as development tools for the system because of the advantages of each tool. Abode Photoshop 5.0 will be used to modify the image and graphics. Chinese input software is also required for the system either "Chinese star" or "NJSTAR Communicator" can be used to input the Chinese words. User interface of system will user-friendly to easy the user, the system need not any user input except of quiz section. Common button supply in every part of system been using by user.